Therapeutic Innovation in Pediatric Neuroblastoma: Age and Stage-Specific Strategies from Prenatal to Early Childhood-A Review Article - Jenabzade, Alireza; Alavi, Samin; Aminasnafi, Ali (Iranian Journal of Child Neurology, 2025)
Neuroblastoma is one of the most common pediatric cancers, predominantly affecting young children. Despite progress in initial treatments, high-risk cases remain challenging due to frequent relapse or resistance, with long-term survival for relapsed or refractory neuroblastoma below 20%. This highlights an urgent need for novel therapies. Emerging approaches such as GD2-targeted immunotherapy with monoclonal antibodies like dinutuximab, CAR-T cell therapy, 131I-MIBG and Lutetium-177-Dotatate radionuclide treatments, metronomic chemotherapy, oncolytic virotherapy, and tailored chemotherapy are showing promise, with autologous stem cell transplantation (ASCT) becoming integral to multimodal regimens. However, challenges persist, including treatment-related toxicity, tumor resistance, and the logistical limitations of personalized medicine. The future of neuroblastoma treatment lies in exploiting genomic profiling, biomarkers, and combinatorial strategies like immunotherapy paired with radionuclide therapy. Rigorous clinical trials will be key to refining these innovations and establishing protocols for widespread use. In summary, advancements in therapy offer hope, yet achieving durable remissions and improved survival still demands intensive research innovation to address current gaps and resistance mechanisms in this complex pediatric malignancy.